Uma análise das repercussões do Programa Nacional do Livro Didático no Livro Didático de Matemática - Nora Olinda Cabrera Zuniga (2007)
This research belongs to the Curriculum and Mathematics Education areas, and focus on the curriculum of textbooks of Mathematics used in elementary school education from 5th to 8th year. The goal is to detect, analyse and understand repercussions of the National Program of Textbook (PNLD) on the curriculum of textbooks, between the PNLD 1999 and PNLD 2005 period. We present an analysis relating three levels of a dynamics of the repercussions in the curriculum of textbooks, developed through the analysis of oficial documents, databases, institucional web sites, semi- structured interviews with autors and evaluators of textbooks that participated in the PNLD, as well as through a case study of one textbook. In the first level, rather external to the textbook, we deal with the relations between the official regulation of the Program and the editors' sphere. In the second level, we revisit the problem of the quality of the textbook, which is officialy posed as the existence of a curricular distance between the textbook and a curricular proposal that emerged when the first evaluations took place. Finally, in the third level, more internal to the textbook, we analyse a set of repercussions in the curriculum of a specific textbook selected as case study, relating it to the expectations of shortening the above-mentioned curricular distance. In the case study, we show in detail how the repercussions, revealed by the changes and remains observed in the textbook, relate to both adhesion and resistance of the author to the official expectations. Moreover, we aprehend the dynamics of these repercussions by analyzing a particular recontextualization of the oficial discourse by the textbook discourse: the author of the textbook chose to also take care of another curricular distance, the one beetween the curriculum of the textbook and the curriculum supposedly practiced in the classroom. We conclude that this specific re-contextualization is part of a broader re- contextualization of the official discourse, which is estimulated by the Government through the regulation of the participation of the social actors involved in the PNLD and made evident by the diversity of textbooks included in each realization of the Program. As we go through the three levels of analysis, we clarify the dynamics of the repercussions, in both directions: society-textbook, and textbook-society, which is one of the most relevant methodological contributions of this research.